Pendidikan Kesehatan tentang Terapi Komplementer dalam Kehamilan - Fatihatul Hayati (Jurnal Abdimas Kesehatan (JAK), 2021)
Complementary therapy in health care is a non-conventional treatment aimed at increasing the degree of public health. The terpi includes promotional, preventive, curative, and rehabilitative efforts that have proven their quality of safety, and effectiveness based on research and science (Evidence Based Medicine). In complementary therapy, the therapist treats various diseases or complaints using traditional techniques and is not done by surgery and drugs or pharmaceutical products, but by utilizing various types of therapy and herbs.The use of complementary therapies in the field of midwifery must be proven safe by research. Pregnant women are a group that is recommended to take advantage of complementary therapy or medicine in dealing with perceived complaints, because complementary therapy can avoid the side effects of conventional medicine and have great control over their own health. Although traditional / complementary medicine is relatively safer, it does not mean that it does not pose a risk, therefore pregnant women must have adequate knowledge about the use of safe complementary therapies during pregnancy.Health education on complementary therapies in pregnancy is provided by extension methods when pregnant women carry out motherhood classes in the working area of Puskesmas Putri Ayu, Jambi City. This activity was carried out in conjunction with the clinical practice of students of D III Midwifery Stikes Baiturrahim Jambi.